2013
DOI: 10.4012/dmj.2012-324
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization on chemically synthesized collagen containing immobilized poly-γ-glutamic acid

Abstract: Chemically synthesized collagen with a triple helix structure similar to that of natural collagen is attractive as a safe biomaterial. Hybrids of chemically synthesized collagen and apatite are proposed for novel bone substitutes. However their apatite-forming ability in simulated body fluid is still quite low. We examined acceleration of apatite formation on collagen by immobilized poly-γ-glutamic acid (PGA), which has excellent apatite-forming ability. Apatite was formed within 3 days when collagen was treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…18,21 The use of g-PGA for bone and nervous system regeneration has already been reported. 20,26 However, g-PGA potential for cartilage regeneration is far from being explored. Chang et al developed g-PGA-graft-chondroitin sulfate-blend-poly(e-caprolactone) scaffolds that were shown to support rat articular chondrocyte culture for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,21 The use of g-PGA for bone and nervous system regeneration has already been reported. 20,26 However, g-PGA potential for cartilage regeneration is far from being explored. Chang et al developed g-PGA-graft-chondroitin sulfate-blend-poly(e-caprolactone) scaffolds that were shown to support rat articular chondrocyte culture for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Its application in the biomedical field has been growing, as observed by its use in biological adhesives, chelating agents for imaging techniques, vaccines, drug/gene delivery systems, and TE-scaffolds, particularly for bone and the nervous system. [18][19][20][21] In the case of bone, g-PGA has been combined with collagen (Col) in the form of g-PGA/Col sponges. Thus, g-PGA modification was shown to increase calcium deposits and apatite formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to appropriate mechanical properties, spontaneous biomineralization is an indispensable property for hydrogels used in bone tissue engineering. Previous studies reported that PGA-based hydrogels exhibited an excellent apatite-forming ability in simulated body fluid (SBF), because abundant −COOH of PGA are effective for heterogeneous apatite nucleation. For instance, Ohtsuki and Miyazaki et al studied biomineralization behaviors of PGA-based hydrogels prepared by covalent cross-linking based on N -hydroxysuccinimide and 1-ethyl-3-(3-(dimethylamino)­propyl)-carbodiimide. Upon soaking in simulated body fluid (SBF), apatite was observed on the surface of PGA-based hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our group recently demonstrated that crosslinked poly-γ-glutamic acid (γ-PGA) can be used to induce bone-like apatite layers in SBF [22][23][24] . Taken together, these findings suggest that the immobilization of γ-PGA onto a Co-Cr alloy constructed from SAMs could be used to increase the bioactivity of the alloy.…”
Section: Introductionmentioning
confidence: 99%